Type 1 Idiopathic Macular Telangiectasia Associated with Type 3 Neovascularization - Tilleul, Julien (Case Rep Ophthalmol, 2014)
PURPOSE: To report the case of a patient with unilateral idiopathic macular telangiectasia (IMT) associated with type 3 neovascularization. METHODS: Observational case report. RESULTS: We describe a case of an 85-year-old woman who presented at our department with a gradual vision loss in her left eye (LE). Her best-corrected visual acuity (BCVA) was 20/200 in the LE. Fundus examination showed 2 small hemorrhages located nasally to the LE fovea, as well as lipid exudates. Fluorescein angiography revealed early hyperfluorescence corresponding to the dilated capillaries. Spectral-domain optical coherence tomography (SD-OCT) showed several microaneurysms within the inner retinal layers. Late indocyanine green angiography revealed a focal hyperfluorescence corresponding to a type 3 neovascularization. No signs of IMT or type 3 neovascularization were detected in the right eye. Based on these findings, the patient was diagnosed with type 1 IMT and coincident type 3 neovascularization. The LE was treated with intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections. Twenty-four months later, SD-OCT revealed regression of the exudative signs, and LE BCVA improved to 20/100. CONCLUSION: We describe the case of an unusual association between older-onset IMT and type 3 neovascularization, and subsequent regression by anti-VEGF injections. We propose a new IMT subtype called type 1C for this association. Further research must be done in order to establish the pathophysiologic mechanism and likelihood of this association.